Factors to consider when applying transcranial magnetic stimulation of dorsolateral prefrontal cortex when resting motor threshold is asymmetric: A case study. Issue 2 (11th February 2016) - Maller, Jerome J.; Thomson, Richard H.S.; McQueen, Susan; Elliot, David; Fitzgerald, Paul B.
Abstract : Transcranial magnetic stimulation (TMS) is an increasingly popular tool in treating psychiatric conditions. The dorsal lateral prefrontal cortex (DLPFC) is typically targeted for stimulation, with magnetic field intensity being calibrated by establishing resting motor threshold (RMT) at hand region of primary motor cortex (M1 hand). This presumes that scalp‐to‐cortex distance (SCD) and cortical thickness is similar at both sites. We present data from a patient who had very asymmetrical RMTs (47 and 78). We investigated SCDs in this patient at the M1 hand and DLPFC, and the M1 hand cortical thickness. We also investigated TMS electric field distribution. The M1 hand SCD and cortical thickness of the M1 hand was larger on the side with higher RMT. Electric field finite element modelling demonstrated the focal point did not effectively reach the M1 hand with higher RMT as the postcentral gyrus was shunting it. Hence, successful DLPFC treatment was based upon the side with lower RMT. This study highlights the importance of tailoring DLPFC treatment intensity not only based on RMT at the M1 hand, and upon the degree to which SCD distance differs between sites, but also based upon size, shape, and density of M1 hand, as well as electric field distribution. Bioelectromagnetics. 37:130–135, 2016. © 2016 Wiley Periodicals, Inc.